ETYMOLOGICAL ANALYSIS OF PLACE NAMES IN SOE – TIMOR ISLAND - Marcelinus Yeri Fernandez Akoli; Yanpitherzon Liunokas; Silviana E. Bako (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
This paper aims at describing the etymological meanings of places inside Soe as well as the morphological processes in forming place names in Soe. This research is a part of the writers’ concern about the decline of local people’s knowledge about their surroundings. There are 21 places’ names under investigation although it is also acknowledged that there are some other places’ names that we have not covered them yet. Result shows that the places’ names are taken from Uab Meto language. Those names are originated either from typical geographical situations of those places or historical events. In particular, the majority of the places’ names refer to springs or water sources to represent survivability of the people as shown 8 places’ names. Moreover, there are two morphological processes involved in those places’ names. They are compounding and affixation. In fact, 19 of the 21 places’ names can be morphologically grouped into endocentric compounds and the other two places’ names belong to affixation process. Realising that this kind of knowledge is something local people in Soe have paid less attention to, it is strongly suggested that this knowledge should be strengthened by imposing it in Soe local curriculum, i.e, local content.